2009
DOI: 10.1371/annotation/e14952c5-b2db-4ff7-976d-6c794d275703
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Use of Integrated Malaria Management Reduces Malaria in Kenya

Abstract: Background: During an entomological survey in preparation for malaria control interventions in Mwea division, the number of malaria cases at the Kimbimbi sub-district hospital was in a steady decline. The underlying factors for this reduction were unknown and needed to be identified before any malaria intervention tools were deployed in the area. We therefore set out to investigate the potential factors that could have contributed to the decline of malaria cases in the hospital by analyzing the malaria control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Azolla pinnata is commonly known as a mosquito weed that has been used for paddy growth nourishments [15]. It provides nitrogen sources for paddy plants and forms a thick mat layer on the water surface, which may prevent the breeding of mosquitoes [15]. Meanwhile, A. pinnata field study has reported that the breeding of malaria-transmitting mosquitoes was completely suppressed in pools, wells, and ponds [16].…”
Section: Introductionmentioning
confidence: 99%
“…Azolla pinnata is commonly known as a mosquito weed that has been used for paddy growth nourishments [15]. It provides nitrogen sources for paddy plants and forms a thick mat layer on the water surface, which may prevent the breeding of mosquitoes [15]. Meanwhile, A. pinnata field study has reported that the breeding of malaria-transmitting mosquitoes was completely suppressed in pools, wells, and ponds [16].…”
Section: Introductionmentioning
confidence: 99%